Screening of Antimicrobial Activity of Vetiver Extracts against Certain Pathogenic Microorganisms - Sangeetha, D (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT In the present study, the Vetiver (leaves, roots) extracts were prepared by using various solvents viz., methanol, chloroform, hexane by Soxhelet apparatus. The extracts were evaporated to dryness and stored in a refrigerator at 4Â°C for future use. The antifungal, antibacterial activity of Vetiver extracts (10.00 mg/ml) were determined by Disc diffusion method. The Minimum inhibitory concentration (MIC) of the extracts (40, 20, 10, 5, 2.50. 1.25 mg/ml) were tested by broth dilution method. The Ampicillin (5 Âµg/ml) and Flucanozole (100 units/disc) were used as positive controls for bacteria and fungi respectively. The disc containing 5% DMSO alone used as blind control. The highest mean zone of inhibition (29 mm and 32 mm) was observed in methanol vetiver extracts of leaves and roots respectively against Staphylococcus aureus. Among the tested fungal cultures, Aspergillus niger exhibit a highest mean zone of inhibition (30 mm and 32 mm) against Vetiver leaves and root extract. The highest minimum inhibitory concentration (MIC) was obtained in methanol extracts of Vetiver against Staphylococcus aureus and Aspergillus niger.